2017
DOI: 10.1080/08916934.2017.1289181
|View full text |Cite
|
Sign up to set email alerts
|

Type-III interferons and rheumatoid arthritis: Correlation between interferon lambda 1 (interleukin 29) and antimutated citrullinated vimentin antibody levels

Abstract: Serum IFNλ1 and IFNλ2 levels are abnormally elevated in patients with RA and the former are linearly associated with circulating anti-MCV antibody levels. These results may place type-III IFN as an attractive new therapeutic target in RA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Type III interferons (IFN-III or IFN-λ) are also produced by pDCs and promote upregulation of genes normally associated with response to IFN-I ( 54 , 62 , 63 ). Furthermore, IFN-III are increased in RA and can associate with disease-specific antibodies ( 64 , 65 ). However, pDCs had comparable IFN-I and IFN-III transcript levels to those in other circulating lymphocyte subsets, and these levels were independent of the background IGS.…”
Section: Discussionmentioning
confidence: 99%
“…Type III interferons (IFN-III or IFN-λ) are also produced by pDCs and promote upregulation of genes normally associated with response to IFN-I ( 54 , 62 , 63 ). Furthermore, IFN-III are increased in RA and can associate with disease-specific antibodies ( 64 , 65 ). However, pDCs had comparable IFN-I and IFN-III transcript levels to those in other circulating lymphocyte subsets, and these levels were independent of the background IGS.…”
Section: Discussionmentioning
confidence: 99%
“…Lv et al 20 found that serum IL-28B levels were significantly lower in RA group than in control group, and speculated that IL-28B may be stimulated by inflammation of joint, may move to the joint cavity to decrease the production of some inflammatory factors including IL-1b, TNF-a and IL-17 and inhibit neutrophil migration to reduce the destruction and inflammation of joint. Furthermore, Castillo-Martinez et al 23 found that IL-28A levels were higher in RA patients with active disease than HCs. Combined with our results, IL-28A and IL-28B expressions in AS patients may have different changes in inflammatory environments.…”
Section: Discussionmentioning
confidence: 98%
“…In a murine model of TLR7-induced lupus, IFNL promotes immune dysregulation through expansion of myeloid and T cell populations in the spleen and blood and induction of chemokine production by keratinocytes (24). Furthermore, IFNL protein levels are upregulated in patients with rheumatoid arthritis (42)(43)(44)(45) and contribute to inflammation and cartilage degradation during osteoarthritis (25). Studies of allergic airway disease, vaccination induced inflammation, and in vitro models examining T cell subtypes reveal the ability of IFNL to inhibit Th2 polarization (26)(27)(28)46) and promote IFNγ production (15,27,28,47), indicating that IFNL may enhance Th1 function (48).…”
Section: Discussionmentioning
confidence: 99%